Using audio to deliver knowledge: Audio is an effective way of delivering agricultural extension information - Schmidt, Cliff; Sullivan, Bartholomew (Technical Centre for Agricultural and Rural Cooperation, 2015)
Audio is an effective way of delivering agricultural extension information